MAKING CONNECTIONS: PSYCHOANALYSIS, ECOLOGY AND DELEUZE AND GUATTARI’S PHILOSOPHIES - Tamboukou, Maria (PINS-Psychology in Society, 2025)
Dodds, Joseph (2011) Psychoanalysis and ecology at the edge of chaos: Complexity theory, Deleuze / Guattari and the psychoanalysis for a climate in crisis. New York & London: Routledge. ISBN 978-0-415-66612-1 pbk. Pages 238. As its title flags up, Psychoanalysis and ecology at the edge of chaos makes a significant contribution to current discussions around the ecological crisis by suggesting that psychoanalysis offers important insights in the problem of climate change and its effects. Now this might initially look like a difficult argument to grasp, but the challenges that the author Joseph Dodds presents us with do not stop here; the second important argument of the book is that psychoanalytic thinking is compatible with and complimentary to Deleuze’s and Guattari’s philosophies. Two plateaus of challenging suggestions and analyses then that I will try to unfold in this review.